KOMUNITAS VESPA EKTREM BAVARIANS DI BANYUWANGI - Widiyanti, Puri Rachma; Suka Arjawa, I Gusti Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The lifestyle of the Vespa community is extreme oriented towards freedom. Vespa was chosen because they were considered to represent their ideology as simple but elegant transportation, different from other motorbike communities that showed their luxury, extreme Vespa children showed the excitement of their motorbikes. In this study the authors took two problem formulations. First, how is the social ritual of the extreme Vespa community child? Second, what is the meaning of the extreme Vespa community social ritual for the Bavarians Extreme Vesarians Community? The purpose of this study was to answer the problem by using qualitative research methods. The theory used is Dick Hebdige's subculture theory. Based on the results of the study, it shows that the Vespa Extreme Bavarians Community has many social rituals, such as extreme Vespa, jamboree, attributes, reggae musik, dreadlocks, togetherness and brotherhood of Vespa communities, solidarity and social service. The rituals they live in are not only limited to activities without meaning, they insert deep meanings, one of which is the desire to win the attention of the public from the worshipers of luxury as well as a way to communicate to the public about the importance of simple living. Keywords: Vespa Extreme Bavarians; social ritual; subculture.